2020
DOI: 10.1002/jcop.22438
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and antecedents of national resilience in Filipino adults during coronavirus crisis

Abstract: Resilience is a broad concept that encompasses individual and social resources to thrive from difficult circumstances. The resilience that occurs as a collective effort or countrywide phenomenon is referred to as national resilience (NR), which connotes the ability of a nation to deal with crises while keeping its social fabric intact. Like the rest of the world, the Philippines has been greatly impacted by the coronavirus pandemic and we argue that a stable and robust NR is needed to bounce back from the chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
(106 reference statements)
2
21
0
Order By: Relevance
“…Participants responded using a 5-point scale (1 = Strongly disagree to 5 = Strongly agree ) , with a higher score indicating a greater level of national resilience. Recent research using Filipino samples showed stable four factors of national resilience (Callueng, Aruta, Antazo, & Diato, 2020 ). Previous studies using Israeli adults demonstrated reliability coefficients of α = .88 (Kimhi, Eshel, et al, 2020a ) and α = .91 (Kimhi, Marciano, et al, 2020b ) for national resilience during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants responded using a 5-point scale (1 = Strongly disagree to 5 = Strongly agree ) , with a higher score indicating a greater level of national resilience. Recent research using Filipino samples showed stable four factors of national resilience (Callueng, Aruta, Antazo, & Diato, 2020 ). Previous studies using Israeli adults demonstrated reliability coefficients of α = .88 (Kimhi, Eshel, et al, 2020a ) and α = .91 (Kimhi, Marciano, et al, 2020b ) for national resilience during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents responded using a 5-point scale (1 = Not at all to 5 = To a very great extent ) with a higher score indicating more severe distress symptoms. Previous research utilized BSI as a valid and reliable tool in assessing distress symptoms in Filipino (Callueng et al, 2020 ) and Jewish Israeli (Kimhi et al, 2019 ) adults. In the current study, CFA solution of the BSI yielded an adequate data fit for a modified single-factor model: χ2 = 69.21, df = 18, p = .00, CFI = .96, TLI = .94, SRMR = .04, RMSEA = .08.…”
Section: Methodsmentioning
confidence: 99%
“…Participants responded to the items on a 5‐point scale, from 1 = not at all to 5 = to a very great extent with a higher score indicating greater distress symptoms. Previous studies utilized the abbreviated BSI as a valid and reliable tool in measuring distress symptoms in Filipino (Callueng et al, 2020 ) and Jewish Israeli (Kimhi, Eshel, et al, 2020a ) adults during the COVID‐19 crisis. In this study, the confirmatory factor analysis (CFA) solution of the abbreviated BSI scale yielded an adequate data fit for a modified single‐factor model: χ 2 = 69.21, df = 18, p = 0.00, comparative fit index (CFI) = 0.96, Tucker–Lewis index (TLI) = 0.94, standardized root mean square residual (SRMR) = 0.04, root mean square error approximation (RMSEA) = 0.08.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the 13‐item National Resilience Scale Short Form (NR‐13; Kimhi & Eshel, 2019 ) has been used to capture individuals' identification with their country, sense of solidarity and social justice, and trust in public institutions (Kimhi & Eshel, 2019 ). Previous research has examined NR in the context of specific adversity or traumatic event such as war and terrorism (Kimhi, Marciano, Eshel, & Adini, 2020a ), natural disasters (Koikari, 2019 ), and the COVID‐19 pandemic (Callueng, Aruta, Antazo, & Briones‐Diato, 2020 ; Kimhi, Marciano, Eshel, & Adini, 2020b ). While NR has been explored in individual countries, studies comparing NR across countries are sparse despite the potential country‐specific factors that may promote or suppress NR (Kimhi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%